Effect of natural ventilation and manual airing on indoor air quality in naturally ventilated Italian classrooms. (March 2016) - Stabile, Luca; Dell'Isola, Marco; Frattolillo, Andrea; Massimo, Angelamaria; Russi, Aldo
Abstract: The present work aimed to evaluate the effect of the ventilation on indoor air quality in Italian classrooms. To this end, schools located in the Central Italy were considered in the survey. The results of two experimental analyses are presented: a) data on classrooms' permeability and resultant air exchange rate, b) trends of indoor air quality parameters during heating and non-heating seasons to assess the possible effect of the manual airing technique. Pressurization tests were performed in 16 classrooms to evaluate their air infiltration due to envelope's leakages. The indoor air quality was investigated in 6 classrooms through CO2, particle number concentration and radon concentration measurements which were also related to the manual airing performed by window opening. Results of the pressurization tests revealed that, even in classrooms characterized by a poor maintenance state, the permeability of the envelopes was too low to guarantee acceptable air exchange rates. The analysis of the classrooms' air quality showed that during the fall and winter seasons the airing was ineffective, while it positively affected the indoor air quality during the spring season when strong reductions in CO2 and radon concentrations were recorded. The effect of the manual airing on the infiltration of outdoor generated pollutants was also assessed. As an example, a greater airing effect resulted in a higher penetration of sub-micrometric particles from outdoor: in fact, particle penetration factors of 0.83 and 1 were measured in fall/winter and spring seasons, respectively. Highlights: Measurements of air permeability and air exchange rates in Italian classrooms. Measurements of indoor air quality (CO2, radon, particle number) in classrooms. High indoor-generated pollutant (CO2, radon) concentrations during the heating season. Reduction of CO2 and radon levels during the non-heating season (airing effect).